Public Interest In Science and Research News - Bonnie Riechert (Journal of Applied Communications, 1983)
More people receive their science news in the print media than in the broadcast media, according to recent research. Studies indicate that while the broadcast media are preferred for sources of some kinds of information, people tend to turn to the print media for complex information.